Intertextuality - Allen, Graham 1963- (Routledge, Taylor & Francis Group, 2022)
1. Origins: Saussure, Bakhtin, Kristeva -- 2. The Text Unbound: Barthes -- 3. Structuralist Approaches: Genette and Riffaterre -- 4. Situated Readers: Bloom, Feminism, Postcolonialism -- 5. Postmodern Conclusions -- 6. Intertextuality Today -- 7. 20 years On
Includes bibliographical references and index
Keywords: Intertextualität; Intertextuality